S7 PLC-based foundation Fieldbus control system using STEP7 and RSFieldbus configuration tools - Thepmanee, Teerawat; Pongswatd, Sawai; Phaerueang, Sarawut (My University, 2014)
This paper presents a technique to configure Foundation Fieldbus devices for process control. The technique applies Foundation Fieldbus (FF) function blocks to cooperate with User-blocks of Siemens PLC. Function Block (FB), Function Call (FC), Data Block (DB) of PLC and FF function blocks are applied to create the assigned control program. In addition, S7 hardware, STEP7 Software, HMI, and OPC are described for hardware configuration, monitoring, diagnostics, and network configuration. The experiment indicates that proposed technique can implement the monitoring and controlling of Foundation Fieldbus Control System (FFCS) with S7 PLC. Moreover, the technique will support end-user to confirm the interoperability concept which avails for low maintenance cost and enhance data available from the field devices. © 2014 ICIC International.
Keywords: Data block; FFCS; Fieldbus function block; Foundation fieldbus; Function call; HMI; OPC; PLC